MEASURING CUSTOMER LOYALTY ANTECEDENTS: THE ROLE OF SATISFACTION AMONG GEN Z COFFEE CONSUMERS - Widya Lestari Bayu; Indrawati; Subhash Kizhakanveatil Bhaskaran Pillai (Jurnal Bisnis dan Akuntansi, 2025)
Indonesia, with a Generation Z population exceeding 66 million in 2023, represents a significant market segment for the food and beverage (F&B) industry. Generation Z exhibits high consumption of food and beverages, making customer loyalty a critical concern for businesses. This study investigates how Corporate Social Responsibility (CSR), product quality, service quality, and price fairness affect customer loyalty, while positioning customer satisfaction as an intervening variable. Data were obtained from 550 purposively selected respondents and processed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that product quality, service quality, and price fairness significantly affect customer satisfaction, which in turn significantly influences customer loyalty. Price fairness not only directly influences customer loyalty but also produces the strongest indirect effect through customer satisfaction (? = 0.189). Meanwhile, CSR significantly affects customer loyalty through a direct path, whereas its impact on customer satisfaction and its indirect influence through satisfaction are not supported. In addition, product quality and service quality do not directly affect customer loyalty but influence it indirectly through customer satisfaction. These findings highlight the role of customer satisfaction as an intervening mechanism linking the key antecedent variables to customer loyalty and provide a context-specific explanation of loyalty formation among Generation Z consumers in the F&B industry.